The Authority and Domination of Kyai in Forming Religious Discourse and Practice in Islamic Boarding Schools - Nauval, Mukhammad Hubbab (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article discusses the authority of the kiai and its dominance in an effort to construct religious discourse and practice in a pesantren. In the reasoning construction of pesantren, kyai is the single figure of the highest authority. On the other side, pesantren is a homogeneous educational institution that allows students (santri) from various socio-religious backgrounds to study religion in one place. The diversity of the background of the santri is very likely to be ignored by the kiai as the holder of the highest religious authority and effect to the practice of domination. In this case, the author conducted a study at the LSQ ar-Rohmah Islamic Boarding School, Bantul, Yogyakarta. This research is a qualitative research using two reading theories, Max Weber's theory of authority and Pierre Bourdieu's theory of dominance. The results of this study indicate that the kiai as the highest authority holder reflects at least two models of authority at once, charismatic authority because of his scientific capacity and traditional authority inherited from his predecessors. As the holder of authority and strengthened by the accumulation of economic capital, culture and symbols, the kiai has full power in formulating, determining and directing religious discourses and practices that take place in pesantren. Meanwhile, santri as a dominated group are only able to practice religious discourses and practices as part of the pesantren curriculum.